Evaluation of Biofilm formation capacity of Pasteurella multocida and its relationship with antibiotic resistance - Kandimalla, Kavitha; Awati, Basavaraj; Putty, Kalyani; Ram, Vamshi Krishna Sai; Yella, Narsimha Reddy; Patil, Nanagouda A; Bhoyar, Ravindra; Choudapur, Mallinath Karabasappa; Karate, Arun; Lunavat, Gopala; Akkaldevi, Jayashri; Ganji, Vishweshwar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Pasteurella multocida is a Gram-negative bacterium that causes haemorrhagic septicaemia in cattle and buffaloes. These organisms are involved in the formation of biofilm and can evade treatment. There is no definitive study to screen the genes associated with biofilm production associated with Pasteurella multocida. The present study describes the real-time PCR based approach for screening of genes associated with biofilm formation. Out of 10 isolates screened for biofilm formation, five of them produced biofilm on Congo red agar of which all are resistant to major antibiotics especially cotrimoxazole, nalidixic acid, enrofloxacin and tetracyclines. All the isolates show presence of genes associated with biofilm formation indicating that other factors influencing the biofilm production. We suggest that the future studies may be targeted to unravel the other factors that influence the biofilm production.